The influence of social capital and financial capability on sustainable competitive advantage through entrepreneurial orientation: Empirical evidence from Small and Medium Industries in Indonesia using PLS-SEM - Febrian, Achmad Fajri; Maulina, Erna; Purnomo, Margo (Advances in Social Sciences Research Journal, 2018)
The inability of Small and Medium Industries (SMIs) to access external financial sources is an obstacle that must be considered. Social capital creates opportunities to get external financial access as financing industrial operations to be able to produce valuable products through entrepreneurial orientation, so SMIs can achieve a sustainable competitive advantage. This paper aims to examine how social capital and financial capability can be new factors to create sustainable competitive advantage through the process of entrepreneurial orientation on SMIs. The data was collected from 110 SMIs on Food Industries Clusters in Bandung, Indonesia. The process of analyzing data using Structural Equation Modeling (SEM) through Partial Least Squares (PLS). The results showed that social capital has no significant effect on entrepreneurial orientation, but social capital will have a significant effect on entrepreneurial orientation if through financial capability, then entrepreneurial orientation has a significant effect on sustainable competitive advantage. This indicates that social capital cannot be directly converted into sustainable competitive advantage. The research findings are that social capital and financial capability will create sustainable competitive advantage if through the entrepreneurial orientation.